2005
DOI: 10.1111/j.1475-1305.2005.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Factors Influencing the Data Derived from a Plug Type Three‐Dimensional Strain Rosette under Compression and Torsion

Abstract: The embedding of three‐dimensional strain rosettes embedded into epoxy models provides an experimental technique for analysing complex structures; however, this technique has been known to produce data that were difficult to explain in terms of their physical significance. To gain a greater insight into the behaviour of a three‐dimensional strain rosette used in this way, a three‐dimensional strain rosette was embedded into each of two separate prismatic bars of square cross‐section and subjected to fundamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Table 3(i) indicates very high values for the sum of the squares for transducer (c) of Figure 1, implying that the sine waves were not very good fits to the data, particularly for gauges 1, 4, 7 and 9. This is thought to be due to the backlash in the frame of the Avery–Dennison testing machine as reported previously [12]. It can also be seen that the orientation of the model in the testing machine radically affects the results.…”
Section: Analysis Of Strain Gauge Datamentioning
confidence: 53%
See 2 more Smart Citations
“…Table 3(i) indicates very high values for the sum of the squares for transducer (c) of Figure 1, implying that the sine waves were not very good fits to the data, particularly for gauges 1, 4, 7 and 9. This is thought to be due to the backlash in the frame of the Avery–Dennison testing machine as reported previously [12]. It can also be seen that the orientation of the model in the testing machine radically affects the results.…”
Section: Analysis Of Strain Gauge Datamentioning
confidence: 53%
“…Considering initially the variance–covariance matrices in Table 1, these do not take into account gauge misalignment errors, as they have a negligible effect on the numbers in the matrices: patterns (a) and (b) which are based on the findings of Ref. [5] and patterns (c) and (d) which are based on the findings of Refs [6, 12], respectively, have the same [ T ′ T ] −1 matrix, where the orthogonal strains have some minor entanglements with covariance terms but the shearing strain terms are completely orthogonal and are bracketed between the transducers of types (e), (f) and (g) designed in Ref. [10] and the new tetrahedron (h).…”
Section: Analysis Of Strain Gauge Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established previously that rotating the bar and fitting sine waves (necessary to eliminate the adverse effects of lack of platen parallelism) [8] and altering the type of transmission element used to transfer load to the bar caused significant departures from the mean values [8]. To determine whether the aforementioned effects, together with carrying out the tests on a different machine and powering all three gauges (refer to Pattern E Figure 1) on a single rosette instead of just one, produced any significant bias, a 2 4 factorial experiment was carried out by repeating the tests twice (see Table 1).…”
Section: Preliminary Tests (A–c)mentioning
confidence: 99%
“…A prismatic bar used in a previous research study [8] was used in this preliminary testing (a similar bar is shown in Figure 3). The prismatic bar (1) with the embedded transducers (2) (four in total: two in front and two behind) was loaded in compression along the z ‐direction via the transmission element (3), which was directly attached to the load cell (25 kN capacity) (4), and the spherical pad (5) was pressed on the prismatic bar.…”
Section: Preliminary Tests (A–c)mentioning
confidence: 99%